EFEKTIVITAS APLIKASI M-HEALTH “HALLO MANIS” BERBASIS ANDROID PADA KEPATUHAN KUNJUNGAN NIFAS - Febriana, Tyas; Runjati,; Sudirman, (Jurnal Kesehatan, 2024)
Coverage of postpartum visits experienced a successive decline since 2018 which affected the increasing postpartum complications supported by the Covid-19 Pandemic situation. Utilization of the application as a medium that can increase the knowledge, attitudes, and behavior of postpartum mothers in conducting postpartum visits. The study aims to develop and to prove the feasibility and effectiveness of the Android-based “Hallo Manis” M-health application in postpartum visit compliance compared to the group that was only given health education with the KIA book (Maternal and Child Health). This study was a Research and Development (R&D) consisting of 5 stages, namely literature study, development design model, validity expert, model trial, and product results with the System Development Life Cycle (SDLC) waterfall method. Types of research is a true experiment post-test type of only control group design. The population of this study was postpartum mothers > 2 hours postpartum. The sampling technique is probability sampling with random cluster sampling and simple random sampling, the sample size is 30 respondents in each group. The average feasibility test result is 86.41% with a p-value of 0.024. "Hallo Manis" application is feasible and effective for postpartum visit compliance with a p-value of <0.0001. This application makes it easy for postpartum mothers to access and obtain information about the postpartum period related to the benefits and objectives of postpartum visits, including reminder notifications including a schedule for postpartum repeat visits so that it helps mothers manage their time.